2016
DOI: 10.1016/j.celrep.2016.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Imprinted Gene Grb10 Promotes Hematopoietic Stem Cell Self-Renewal and Regeneration

Abstract: SUMMARY Imprinted genes are differentially expressed by adult stem cells, but their functions in regulating adult stem cell fate are incompletely understood. Here, we show that growth factor receptor bound protein 10 (Grb10), an imprinted gene, regulates hematopoietic stem cell (HSC) self-renewal and regeneration. Deletion of the maternal allele of Grb10 in mice (Grb10 m/+ mice) substantially increased HSC long-term repopulating capacity compared to Grb10 +/+ mice. Following total body irradiation (TBI), Grb10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…66,67 Studies of Grb10 deficient mice demonstrated Grb10 ’s role in hematopoietic regeneration in vivo . 68 Additionally, in a transcriptome study of CD4+ Effector Memory T cells (CD4 + T EM ), GRB10 was the most significantly downregulated gene after T-cell receptor stimulation. 69 Notably, in both human and mouse, GRB10 mRNA is highly alternatively spliced, resulting in four to seven unique isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…66,67 Studies of Grb10 deficient mice demonstrated Grb10 ’s role in hematopoietic regeneration in vivo . 68 Additionally, in a transcriptome study of CD4+ Effector Memory T cells (CD4 + T EM ), GRB10 was the most significantly downregulated gene after T-cell receptor stimulation. 69 Notably, in both human and mouse, GRB10 mRNA is highly alternatively spliced, resulting in four to seven unique isoforms.…”
Section: Resultsmentioning
confidence: 99%
“…Chemoradiation-based conditioning regimens for HSCT as well as standard induction regimens for hematological malignancies are often associated with cytopenias resulting from the myelosuppressive injury of the endogenous HSPCs. Prior studies have shown that HSPCs undergo mTOR activation during myelosuppressive recovery (Baumgartner et al, 2018) and that mTORC1 inhibition delays hematopoietic recovery (Yan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…qRT-PCR analysis confirmed Grb10 and Tgfbr3 expression were reduced in −77 −/− R1 cells (Figure 6B). The signaling adapter GRB10 is implicated in promoting HSC self-renewal and regeneration (Yan et al, 2016). Tgfbr3 , which encodes TGFβ receptor type III (Wang et al, 1991), is a marker of late BFU-Es (Gao et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The latter genes included Ryk, Tgfbr3 and Grb10 , encoding hematopoietic signaling components (Famili et al, 2016; Gao et al, 2016; Povinelli and Nemeth, 2014; Povinelli et al, 2015; Randrianarison-Huetz et al, 2010; Yan et al, 2016), and other factors not implicated in red cell biology. Based on the large reduction in Ryk expression in −77 −/− R1 cells and reduced CFU activity upon Ryk knockdown, Ryk signaling may constitute an important determinant of erythroid precursor cell maturation and/or function.…”
Section: Discussionmentioning
confidence: 99%